The Concept of Learning Celestial Science in the Book "Wasilah al-Mubtadi'in Fi Risalah al-Qamarain” - Badrun Taman; Doki Hermanto; Agustini; Rindom Harahap; Nur Hidayat (Nusantara Education, 2024)
This study explores the concepts of celestial science education within the work of Muhammad Yunus bin Abdullah, a lesser-known Falak scholar in Indonesia, particularly in East Java, and his book "Risālatil Qamaraīn Fī Ijtimā’in Nayyiraīn." Classified as Taqribi Hisab Hakiki, the book undergoes an extensive content analysis, involving a literature review and qualitative interviews with celestial science experts. The findings indicate that the book "Wasīlah Al Mubtadi’īn Fī Tarjamati Risālatil Kamaraīn Fī Ijtimā’in Nayyiraīn" presents a comprehensive approach to learning celestial science, covering fundamental concepts, intricate calculations of the lunar month initiation, and detailed explanations of astronomical phenomena. Utilizing classical Arabic terms explained in Javanese Arabic (pego), the book maintains a connection with traditional celestial science while ensuring local accessibility. Emphasizing the disparities between sidereal and synodic months, the text integrates practical applications of arithmetic and trigonometric principles. Notably, acknowledging multiple sources indicates a broad approach to celestial science education, and the inclusion of practical information fosters a balance between theoretical and applied knowledge, aligning the study with both classical and modern perspectives in celestial science.